A Protocol to Evaluate Retinal Vascular Response Using Optical Coherence Tomography Angiography - Sousa, David Cordeiro; Leal, Inês; Moreira, Susana; do Vale, Sónia; Silva-Herdade, Ana S.; Aguiar, Patrício; Dionísio, Patrícia; Abegão Pinto, Luís; Castanho, Miguel A. R. B.; Marques-Neves, Carlos (Frontiers in Neuroscience, 2019)
Introduction: Optical coherence tomography angiography (OCT-A) is a novel diagnostic tool with increasing applications in Ophthalmology clinics that provides non-invasive high-resolution imaging of the retinal microvasculature. Our aim is to report in detail an experimental protocol for analysing both vasodilatory and vasoconstriction retinal vascular responses with the available OCT-A technology. Methods: A commercial OCT-A device was used (AngioVue®, Optovue, CA, USA) and all examinations were performed by an experienced technician using the standard protocol for macular examination. Two standardized tests were applied: i) the hypoxia challenge test (HCT) ii) the handgrip test, in order to induce a vasodilatory and vasoconstriction, respectively. OCT-A was performed at baseline conditions and during the stress test. Macular parafoveal vessel density of the superficial and deep plexuses was assessed from the en face angiograms. Statistical analysis was performed using STATA v14.1 and a p < 0.05 was considered for statistical significance. Results: Twenty-four eyes of 24 healthy subjects (10 male) were studied. Mean age was 31.8  8.2 years [range 18-57 years]. Mean parafoveal vessel density in the superficial plexus increased from 54.7  2.6 in baseline conditions to 56.0  2.0 in hypoxia (p<0.01). Mean parafoveal vessel density in the deep plexuses also increased, from 60.4  2.2 at baseline to 61.5  2.1 during hypoxia (p<0.01). The OCT-A during the handgrip test revealed a decrease in vessel density in both superficial (55.5  2.6 to 53.7  2.9, p < 0.001) and deep (60.2  1.8 to 56.7  2.8, p < 0.001) parafoveal plexuses. Discussion: In this work we detail a simple, non-invasive, safe and non-costly protocol to assess a central nervous system vascular response (i.e. the retinal circulation) using OCT-A technology. A vasodilatory and vasoconstriction response were observed in two physiologic conditions – mild hypoxia and isometric exercise, respectively. This protocol constitutes a new way of studying retinal vascular changes which may be applied in health and disease of multiple medical fields.